2021
DOI: 10.1029/2020ja028528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Variability of Night‐Time Equatorial Thermospheric Winds Over Nigeria, West Africa

Abstract: From the work of Delinger (1939), we began to understand that complex behavior of ionospheric currents and electric fields during quiet and magnetically active periods are partly affected by thermospheric neutral parameters such as wind velocity, density, and temperature. The coupling of these modulated ionospheric currents and electric fields due to some of these thermospheric neutral parameters with the F-region and its top side can degrade navigation systems and attenuate radio signals (Panda et al., 2018; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Typical meridional and zonal wind measurements using Fabry Perot Interferometer during diurnal and geomagnetic storm periods over the African region have been studied and analyzed (Kaab et al., 2017; Malki et al., 2018; Rabiu et al., 2021; Tesema et al., 2017). We can comment on the diurnal variation of neutral winds, that is poleward meridional winds in the evening that turn equatorward at around midnight and eastward zonal winds in the evening that turn westward towards the sunrise in the northern winter hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…Typical meridional and zonal wind measurements using Fabry Perot Interferometer during diurnal and geomagnetic storm periods over the African region have been studied and analyzed (Kaab et al., 2017; Malki et al., 2018; Rabiu et al., 2021; Tesema et al., 2017). We can comment on the diurnal variation of neutral winds, that is poleward meridional winds in the evening that turn equatorward at around midnight and eastward zonal winds in the evening that turn westward towards the sunrise in the northern winter hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the longitudinal variation in the drift was related to the changes in the zonal currents driven by meridional winds at F region height of the equatorial ionosphere. It had been recently found that, changes in the thermospheric neutral winds are the reason for the longitudinal differences that have been re-ported in equatorial electric fields between the West and East Africa stations [14] [43] [44]. They found that, in general, the neutral wind speed observed in eastern African sector is weaker and stronger in west African sector compared with speeds observed in other longitude sectors.…”
Section: Discussionmentioning
confidence: 99%
“…The first East African nighttime equatorial thermospheric wind and temperature results show many similarities and differences between Brazil and Peru (Tesema et al., 2017). Another study of the equatorial thermospheric winds was conducted using an FPI located in Nigeria (Rabiu et al., 2021). The results indicated that the zonal winds ranged from −124 to 163 m/s, and the meridional winds ranged from −70 to 95 m/s.…”
Section: Introductionmentioning
confidence: 99%